Menghadapi Tantangan Era Digital, Strategi Integrasi Media Sosial, Literasi Digital dan Inovasi Bisnis - Harry Saptarianto; Shelvi Deviani; Syamas Isti Anah; Indah Noviyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The digital era is an era where an era experiences rapid progress that leads to digital. This era is characterized by fast and easy access to information. Technology that is developing more rapidly has brought many significant changes. This research uses the literature review method. Literature review is a description of theories, findings, other research materials obtained by analyzing the results of publications such as books, research articles or others related to research questions that have been prepared previously. Facing the challenges of the digital era requires several strategies such as social media integration strategies, digital literacy and business innovation. Business people are expected to be able to evaluate technology which is increasingly developing rapidly. They can't just rely on offline business. The development of the digital era has had a significant influence on every aspect of life. What is felt is the ease of access to information which is driven by the development of technology, making it easier for every human activity in various fields including education, trade and health.